Correlation between vitamin D deficiency and fasting blood glucose levels in obese children. (August 2021) - Juliaty, Aidah; Mutmainnah; Daud, Dasril; Lisal, Johan Setyawan
Summary: Background: This study aimed to determine the relationship between Deficiency of vitamin D and hyperglycemia in children with obesity. Methods: This cross-sectional study was carried out between February and April of 2020. This study's subject population consisted of high school students aged 11 to 17 who were obese. The 25 (OH) level of Vitamin D was determined using the Chemiluminescence Immune Assay method. Subjects were divided into 4 groups; vitamin D deficiency with hyperglycemia, vitamin D deficiency without hyperglycemia, normal vitamin D with hyperglycemia, and normal vitamin D without hyperglycemia. Results: The prevalence of hyperglycemia was 28 (54.9%) in the vitamin D deficiency group and 17 (378%) in the normal vitamin D group, respectively. Statistical analysis revealed no statistically significant difference between the two groups (p = 0.093). With p = 0.031, there was a significant difference in the mean value of fasting blood sugar levels between the two groups. The frequency of hyperglycemia was 54.9 percent in the vitamin D deficiency group and 37.8 percent in the normal vitamin D group. Fasting blood sugar levels were lower in obese children with vitamin D deficiency than in children with normal vitamin D. Conclusion: Fasting blood sugar levels were correlated with vitamin D levels in obese children, but clinically insignificant. However, the research is ongoing, so, it is critical to conduct early screening for Vitamin D and fasting blood sugar levels in order to reduce the risk of metabolic and cardiovascular diseases.